Yearly reduction of glucocorticoid dose by 50% as tapering schedule achieves complete remission for 124 pemphigus vulgaris patients. Issue 3 (1st September 2015) - Wang, Mingyue; Gao, Yu; Peng, Yang; Zhao, Junyu; Chen, Xixue; Zhu, Xuejun
Abstract: Glucocorticoids are the first‐line treatment for pemphigus vulgaris. Among 140 patients receiving systemic glucocorticoids, 124 patients achieved complete remission off or on a prednisone dose of ≤10 mg/day or less for 6 months or more. The mean average steroid controlling doses were 0.65, 0.62, 0.80, 1.08 and 1.38 mg/kg per day for the mucosal‐dominant patients and the mild, moderate, severe and extensive cutaneous‐involved patients, respectively ( P  <   0.001). The mean durations of the initial tapering after controlling doses started were 77.98, 48.78, 31.74 and 28.83 days when the disease was controlled with doses of 40 mg/day or less, 45–60 mg/day, 65–80 mg/day and more than 80 mg/day for the cutaneous‐involved types, respectively ( P  <   0.005). Of the patients, 79.51% achieved complete remission within 3 years, 98.36% within 5 years and all within 6 years, which corresponded to a 50% yearly reduction of glucocorticoid dose. These successfully treated patients indicate that a severity‐tailored initial dose of glucocorticoids, an initial tapering duration based on the initial dose and a subsequent 50% yearly tapering regimen may cure pemphigus vulgaris within 3–6 years.